Constructing Selenium Nanoparticles with Enhanced Storage Stability and Antioxidant Activities via Conformational Transition of Curdlan - Xindong Xu; Yuxue Pan; Xiaoying Liu; Zhong Han; Shan Chen (Foods, 2023)
Selenium nanoparticles (SeNPs) are among the emerging selenium supplements because of their high bioactivity and low toxicity. However, bare SeNPs are prone to activity loss caused by aggregation and sedimentation. This study aims to stabilize SeNPs with curdlan (CUR), a polysaccharide, to maintain or even enhance their biological activity. Herein, the stable SeNPs were constructed via the unique conformational transition of CUR induced by alkali-neutralization (AN) pretreatment. The physicochemical properties and structures of the prepared SeNPs were characterized by dynamic light scattering (DLS), UV-visible spectroscopy, Fourier-transform infrared spectroscopy (FTIR), X-ray diffraction (XRD), transmission electron microscopy (TEM), and free-radical-scavenging activity assays. The results show that most SeNPs are stabilized within the triple helix of CUR that has been pretreated with high-intensity AN treatment. These amorphous, small-sized (average size was 53.6 ± 17.7 nm), and stabilized SeNPs have significantly enhanced free-radical-scavenging ability compared to the control and can be well-stabilized for at least 240 days at 4 °C. This work indicates that CUR, as a food additive, can be used to well-stabilize SeNPs by AN pretreatment and provides a facile method to prepare and enhance the stability and bioactivity of SeNPs via triple-helix conformational transition.